Hubungan Peran Keluarga Dan Koping Keluarga Dengan Tingkat Kekambuhan Pada Pasien Skizofrenia di Wilayah Kerja Puskesmas Bogatama - Marisca Agustina; Novi Julia; Aisyah Safitri (STIKES Columbia Asia Medan, 2024)
Schizophrenia is a mental disorder that causes a person to lose their minds and find it difficult to understand what they are thinking, causing hallucinations and behaving unnaturally. The recovery period in these patients can be extended if they have a close relationship with their family because it becomes a therapeutic attitude and a form of support for the patient. The purpose of the study was to determine the relationship between family roles and family coping with the relapse rate in schizophrenia patients in the Bogatama Health Center Work Area. The design of this study was descriptive correlation with a cross sectional approach. The population of this study was an entire family that had family members with schizophrenia as many as 35 people. The research sample is the entire population using total sampling techniques. The data collection tool used is a questionnaire that has been tested for validity and reliability and uses a checklist sheet. The results of the study are known to be the relationship of family roles with relapse rates in schizophrenia patients with a p-value = 0.003, and the relationship of coping with relapse rates with a p-value of 0.001. The conclusion p-value < α (0.05). Conclusion There is a relationship between family roles and family coping with relapse rates in schizophrenia patients in the Bogatama Health Center Work Area.